Nowe media jako przestrzeń rywalizacji politycznej na przykładzie kampanii prezydenckich w Polsce w latach 1995-2015 - Stoppel, Anna (My University, 2018)
W państwach demokratycznych, opartych na politycznym pluralizmie i konkurencji, głównym celem aktorów politycznych jest walka o władzę lub jej utrzymanie. Naturalnym działaniem jest zatem dążenie do maksymalizowania korzyści w tym obszarze. W praktyce politycznej stosuje się nowe techniki i metody oddziaływania na obywateli, aby zyskać poparcie dla siebie, swojej oferty, a w rezultacie osiągnąć sukces wyborczy. Nowe media stały się niezwykle ważną przestrzenią rywalizacji politycznej. Za główny cel pracy przyjęto określenie roli (w tym sposobów i efektów wykorzystania) nowych mediów (głównie Internetu) w rywalizacji politycznej na przykładzie polskich prezydenckich kampanii wyborczych w latach 1995-2015. Wspomniany wyżej cel podzielony został na następujące cele szczegółowe: - analiza wykorzystania nowych mediów w sferze polityki; - analiza porównawcza działań komitetów wyborczych kandydatów na urząd prezydenta RP w zakresie wykorzystania nowych mediów w praktyce prezydenckich kampanii wyborczych (w kontekście działań informujących, mobilizujących, angażujących wyborców); - określenie efektów wykorzystania Internetu w prezydenckich kampaniach wyborczych; - zbadanie, jak na przestrzeni lat rozwijały się internetowe narzędzia służące informowaniu obywateli, mobilizowaniu i angażowaniu elektoratu; - próba zarysowania perspektyw wykorzystania nowych mediów w polskich kampaniach wyborczych; - ocena ich roli w procesie rywalizacji o głosy wyborców na polskiej scenie politycznej. Główną hipotezą badawczą sformułowaną na potrzeby dysertacji jest założenie, że: w rywalizacji politycznej 2015 r. nowe media wykorzystane zostały w większym zakresie niż we wcześniejszych kampaniach wyborczych, towarzyszących prezydenckim elekcjom, a media społecznościowe były najbardziej popularnym i jednocześnie efektywnym narzędziem rywalizacji politycznej. Narzędzia polityki 2.0. i 3.0., za sprawą swego angażującego i mobilizującego wyborców potencjału, zmieniły zarówno wymiar komunikacji politycznej, jak i w znaczący sposób zmodyfikowały wyborcze strategie komunikacyjne i finansowe. Zmian tych jednak nie można określać mianem rewolucji. Mają one ewolucyjny charakter.

One of the most important problems of modern civilization are issues related to the functioning of contemporary democracy, which is characterized by the participation of citizens in the exercise of power and political competition. The new media became in this context a great platform for information, involvement and mobilization activities of the electorate. It means that during the years analyzed in the thesis, the new functions of modern media have been developed, and they seem to differentiate significantly each presidential campaign from the previous one. Information and communication technologies have found wide application in electoral strategies - however, this mainly concerns the last two elections. The Polish presidential campaigns of recent years have become for researchers interested in the context of development of new media and their implementation in the field of politics. The research subject of the thesis is the use of new media in political rivalry as part of election campaigns for the office of the President of the Republic of Poland. In the dissertation, it was decided to determine the role of the new media in presidential election campaigns and to indicate their impact on the shape and course of political rivalry, taking place as part of election campaigns before elections for the office of President of the Republic of Poland in 1995-2015. The research problem thus undertaken seems to be extremely important from the point of view of political sciences. The main goal of the thesis was to define the role of new media (mainly the Internet) in political rivalry on the example of Polish presidential electoral campaigns in the years 1995-2015. The main objective has been divided into the following specific goals: - analysis of the use of new media in the sphere of politics; - comparative analysis of the activities of election committees of candidates for the office of the President of the Republic of Poland in the use of new media in the practice of presidential electoral campaigns (in the processes of informing, mobilizing and involving voters); - identifying the effects of using of the Internet in presidential election campaigns; - examining how Internet tools for informing, mobilizing and engaging the electorate have developed over the years; - indicating the prospects for using new media in Polish election campaigns; - assessment of their role in the process of rivalry for the votes of voters on the Polish political scene. Such an approach to research objectives should guarantee the analysis of all the most important issues of the subject of the thesis.
New media as a space for political rivalry on the example of presidential campaigns in Poland in 1995-2015
Wydział Nauk Politycznych i Dziennikarstwa
Keywords: nowe media; new media; komunikowanie polityczne; political communication; kampania wyborcza on-line; online election campaign; rywalizacja polityczna; political rivalry; Internet